Answer:
f(1)=4
Step-by-step explanation:
f(1)=3(1)^4-(1)^2+4(1)-2
f(1)=3(1)-1+4-2
f(1)=3-1+4-2
f(1)=4
Answer:
f(-5)=28
Step-by-step explanation:
f(x)=x²-2x-7
f(-5) means that we have to replace x by -5.
f(-5)=(-5)²-2(-5)-7=25+10-7=25+3=28
Answer:
-2
Step-by-step explanation:
2(x-3), x=2
Since we know what x equals, plug it into the equation
2(2-3)
2(-1)
-2
<u>Answer:</u>
The answer is D : 4.
<u>Step-by-step explanation:</u>
<em>=2x-3>11-5x</em>
<em>=2x-3+5x>11</em>
<em>=7x-3>11</em>
<em>=7x>11+3</em>
<em>=7x>14</em>
<em>=7x/7>14/7</em>
<em>=x>2</em>
<em />
<em />
<em>By simplifying the problem, you can see that "x" </em><em><u>must</u></em><em> be greater than 2. Therefore, eliminating all other possible answers that are shown, but 4. </em>
<em />
<em />
<em>I answered the same questions with the same exact wording and explanation so please don't report any answers that are the same as this one, they are all mine and written by me. </em>